Effective Use of AI-Driven Third-Party Frameworks in Mobile Apps - Vijay Bhasker Reddy Bhimanapati; Prof. (Dr.) Punit Goel; A Renuka (Innovative Research Thoughts, 2021)
The integration of Artificial Intelligence (AI) into mobile applications has significantly advanced the capabilities of modern software, enhancing user experiences through personalized, intelligent interactions. The effective use of AI-driven third-party frameworks has emerged as a pivotal strategy for developers aiming to leverage AI's potential without the need for extensive in-house expertise. This paper explores the impact and benefits of incorporating AI-driven third-party frameworks into mobile app development, focusing on their role in optimizing performance, enhancing user engagement, and accelerating development cycles. AI-driven third-party frameworks offer a range of pre-built functionalities, including natural language processing (NLP), image recognition, and predictive analytics, which can be seamlessly integrated into mobile applications. These frameworks provide developers with powerful tools to implement advanced features with reduced time and resource investment. By utilizing these frameworks, developers can focus on core application functionalities while benefiting from sophisticated AI capabilities that would otherwise require significant development effort.